BCSH/BSBMT/UK clinical virology network guideline: diagnosis and management of common respiratory viral infections in patients undergoing treatment for haematological malignancies or stem cell transplantation. (7th April 2016) - Dignan, Fiona L.; Clark, Andrew; Aitken, Celia; Gilleece, Maria; Jayakar, Vishal; Krishnamurthy, Pramila; Pagliuca, Antonio; Potter, Michael N.; Shaw, Bronwen; Skinner, Roderick; Turner, Andrew; Wynn, Robert F.; et al.
Summary: A joint working group established by the Haemato‐oncology subgroup of the British Committee for Standards in Haematology, the British Society for Bone Marrow Transplantation and the UK Clinical Virology Network has reviewed the available literature and made recommendations for the diagnosis and management of respiratory viral infections in patients with haematological malignancies or those undergoing haematopoietic stem cell transplantation. This guideline includes recommendations for the diagnosis, prevention and treatment of respiratory viral infections in adults and children. The suggestions and recommendations are primarily intended for physicians practising in the United Kingdom.